2016
DOI: 10.1158/1535-7163.mct-16-0092
|View full text |Cite
|
Sign up to set email alerts
|

Alterative Expression and Localization of Profilin 1/VASPpS157 and Cofilin 1/VASPpS239 Regulates Metastatic Growth and Is Modified by DHA Supplementation

Abstract: Profilin 1, cofilin 1, and vasodialator stimulated phosphoprotein (VASP) are actin binding proteins (ABP) which regulate actin remodelling and facilitate cancer cell metastases. MiR~17–92 is highly expressed in metastatic tumors and profilin1 and cofilin1 are predicted targets. Docosahexaenoic acid (DHA) inhibits cancer cell proliferation and adhesion. These studies tested the hypothesis that the metastatic phenotype is driven by changes in ABPs including alternative phosphorylation and/or changes in subcellul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
3
18
1
Order By: Relevance
“…60 Significantly increased pVASP-S239 levels in cancer cells and tissue counter high actin polymerization, hyperproliferation, invasion, and migration. 13,15,40,61 As shown by our data, increased levels of VASP, pVASP-S239, and cofilin-1 in the context of increased F-actin content suggest a regulatory role of these proteins to counteract trophoblast hypermigration and proliferation. Docosahexaenoic acid reduces cancer cell aggressiveness, which is associated with changes in actin dynamics and apoptotic profiles.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…60 Significantly increased pVASP-S239 levels in cancer cells and tissue counter high actin polymerization, hyperproliferation, invasion, and migration. 13,15,40,61 As shown by our data, increased levels of VASP, pVASP-S239, and cofilin-1 in the context of increased F-actin content suggest a regulatory role of these proteins to counteract trophoblast hypermigration and proliferation. Docosahexaenoic acid reduces cancer cell aggressiveness, which is associated with changes in actin dynamics and apoptotic profiles.…”
Section: Discussionsupporting
confidence: 70%
“…[34][35][36][37][38][39] Moreover, cofilin-1 levels vary among cancer cell and tumor types and degree of proliferation and migration. 26,[40][41][42] Docosahexaenoic acid (DHA), an anti-inflammatory omega-3 fatty acid often taken as a dietary supplement, has been suggested as a pharmacologic agent in placental disorders, which are often associated with inflammation. [43][44][45][46][47] This suggestion has pathophysiologic plausibility because DHA inhibits cancer cell proliferation, migration, invasion, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Of note is the observation that PA4 caused nuclear localization of phosphorylated VASP and PA5 cytoplasmic localization. It is reasonable to assume that the different effects attributable to pVASP may correlate with different localization of the protein, as previously reported [ 41 , 42 ], but at the moment, we cannot ascertain whether phosphorylation at S239 happens in the cytoplasm or directly inside the nucleus and we cannot define the role of pVASP in the two cellular compartments. Effects on migration in MNT1 cells could not be tested, but PA4 treatment induced an increase of S239 pVASP with nuclear localization and a decrease in S157 pVASP.…”
Section: Discussionmentioning
confidence: 80%
“…With the advancement of precise medical theories and advances in technology, the research of miR-17-92 cluster has continued to deepen in tumor cells, particularly, the roles of miR-17-92 cluster have been continuously explored in lung cancer. Furthermore, the new study has observed that Docosahexaenoic acid (DHA), as a novel therapeutic, modulates expression of miR-17-92 and inhibits cell migration and viability in lung cancer 76 . Intriguingly, accumulating studies show that the roles of miR-17-92 cluster are not clear in lung cancer and need to explore continually in the future.…”
Section: Conclusion and Perspectivementioning
confidence: 99%